El plagio académico: Un enfoque integral - Guardia, Candy; Yupanqui Esquivel, Miguel Tupac; Bizarro, Wilfredo; De La Cruz–Urrutia, Lucia; Vargas-Portugal, Kevin (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
Plagiarism in science is a serious breach of ethics and can have serious consequences for the reputation and career of the scientists involved. The book examines the causes and factors that contribute to plagiarism, including social and cultural pressures, lack of academic skills, technological factors, and student attitudes and perceptions. Plagiarism detection is also covered in detail, including tools and techniques to detect it, the teacher’s role in prevention and detection, and strategies to verify the originality of work.